Analisis Pengaruh Intellectual Capital Terhadap Firm Value dengan Roa sebagai Variabel Moderasi (Studi Empiris pada Sub Sektor Perbankan yang Terdaftar Di BEI Tahun 2012-2016) - Zulkarnain Zulkarnain; Siti Annisa Failasufi (Institut Manajemen Wiyata Indonesia, 2020)
This research aims to analyze influence of intellectual capital on firm value with ROA as a moderating variable in banking companies in Indonesia. This research uses intellectual capital value added consisting of VACA, VAHU, and STVA as independent variable. This research also examines the relationship between intellectual capital and firm values which are moderated by financial ratios. The financial ratio used is return on assets which is used as a moderating variable. The samples consisted of 14 companies listed on the Indonesia Stock Exchange and published their financial statement in the 2012-2016 period. The data was used in this research was the secondary data and selected by using purposive techniques. The analysis implement that used was the linear regression analysis at a 5% significance level. The results of this research provides evidence that intellectual capital value added which is the sum of VACA, VAHU, and STVA has a positive effect on the value of the firm by being moderated by ROA. Based on the results of this research, it was also provides evidence that intellectual capital affects the value of the firm by moderating ROA.